Evaluating the Role of Social Norms in Fostering Pro-Environmental Behaviors - Perry, George L.W.; Richardson, Sarah J.; Harré, Niki; Hodges, Dave; Lyver, Phil O’B.; Maseyk, Fleur J.F.; Taylor, Riki; Todd, Jacqui H.; Tylianakis, Jason M.; Yletyinen, Johanna; Brower, Ann (Frontiers in Environmental Science, 2021)
Human activity is changing the biosphere in unprecedented ways, and addressing this challenge will require changes in individual and community patterns of behaviour. One approach to managing individual behaviours is ‘top-down’ and involves imposing sanctions through legislative frameworks. However, of itself, a top-down framework does not appear sufficient to induce the changes required to meet environmental sustainability targets. Thus, there has been interest in changing individual-level behaviour from the ‘bottom-up’ by, for example, fostering desirable pro-environmental behaviours via social norms. Social norms arise from expectations about how others will behave and the consequences of conforming to or departing from them. Meta-analyses suggest that social norms can promote pro-environmental behaviour. Environmental social norms that appear to have both changed in recent decades and have themselves promoted change include recycling, and nascent behavioural shifts such as the move away from single-use plastics and flight shaming. However, whether the conditions under which pro-environmental social norms emerge and are adhered align with the features of environmental systems is unclear. Furthermore, individuals might feel powerless in a global system. This feeling of powerlessness, or lack of self-efficacy, may limit the growth of norms. We review the conditions believed to promote the development of and adherence to social norms, then consider how those conditions relate to the environmental challenges of the Anthropocene. While promoting social norms has a valuable role to play in promoting environmental actions, we conclude that norms are most effective where individual actions are immediately evident and have an obvious and local effect.